Insight into electrochemical performance of porous FexSiy intermetallic anode for zinc electrowinning. (June 2020) - Shen, Botao; He, Yuehui; Li, Wenhao; Wang, Zhonghe; Yu, Linping; Jiang, Yao; Liu, Xinli; Kang, Jiangang; Gao, Haiyan; Lin, Nan
Abstract: Pb pollution, which is provoked by lead-based anodes in large-scale industrial production, has seriously endangered human health and destroyed the ecological environment in the past decades. In this work, environmentally friendly porous Fex Siy intermetallics are prepared by elemental powder reactive synthesis as anodes in zinc electrowinning for the first time. The as-prepared porous Fex Siy anodes (Fe3 Si, Fe5 Si3, and FeSi) have been investigated in terms of electrochemical performance. Among the three anodes, porous Fe5 Si3 anode shows relatively better comprehensive properties in 160 g·L −1 H2 SO4 . Porous Fe5 Si3 anode exhibits electrocatalytic activity and long-term stability under the condition of zinc electrowinning, which guarantees a service life up to 400 h. The activity for OER shows that porous Fe5 Si3 anode is delivering an overpotential of 1.072 V and tafel slope of 326.6 mV·dec at current density of 50 mA·cm −2 . The electrocatalytic activity is positively correlated with the open porosity. The oxides formed in the anode surface are mainly composed of Fe2 O3 and amorphous SiO2, which protect the anode against corrosion and help to the activity for OER. This result demonstrated that Fe5 Si3 as alternative anode material has potential application value in industry. Graphical abstract: Unlabelled Image Highlights: Fe5 Si3 with good pore structure is prepared by reactive synthesis. Lead-free and high-purity deposited zinc is obtained by porous Fe5 Si3 anode in ZEW. Porous Fe5 Si3 anode exhibits good OER activity and high stability in strong acid. The formed amorphous SiO2 exhibits good corrosion resistance and OER activity.